Alternatives and perspetives for the knowledge of man - Guzmán Mesa, Eufrasio (Estudios de Filosofía, 1992)
At present, the different attempts at understanding man, as has already been the case in the past, are facing a negative disposition with regards to their results and possibilities: we are referring to the configuration of obscurantist attitudes in culture and in the sciences of man. With this situation in view, sorne altematives are shown, considering them as being strategies of objective knowledge; the relations between the different explicative strategies, in opposition to sorne comprehensional perspectives, are set forth. The distinction nature-culture comes to aid in this case, both in posing the problem and in articulating reflection.